2003
DOI: 10.1023/b:agen.0000029390.09354.f8
|View full text |Cite
|
Sign up to set email alerts
|

Novel Function of Ascorbic Acid as an Angiostatic Factor

Abstract: Endothelial permeability is increased by vascular endothelial cell growth factor and decreased by antioxidants. Whether or not l-ascorbic acid (Asc), which decreases endothelial permeability by stimulating the endothelial barrier function, is anti-angiogenic (angiostatic) remains unknown. We examined the role of Asc on angiogenesis using two assay systems. At first, the potential role of Asc on four steps of angiogenesis was investigated in cultured bovine microvascular endothelial cells. Asc inhibited the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 54 publications
1
37
0
2
Order By: Relevance
“…As shown in figure 2c, VEGF-dependent cell proliferation was completely stopped in the presence of extracellular antioxidants. These results complement studies showing inhibition of endothelial proliferation by antioxidants, although in most studies, intracellular scavengers of ROS have been used [17, 18]. …”
Section: Resultssupporting
confidence: 80%
“…As shown in figure 2c, VEGF-dependent cell proliferation was completely stopped in the presence of extracellular antioxidants. These results complement studies showing inhibition of endothelial proliferation by antioxidants, although in most studies, intracellular scavengers of ROS have been used [17, 18]. …”
Section: Resultssupporting
confidence: 80%
“…Reportedly, H 2 O 2 stimulates angiogenesis in vitro (Yasuda et al, 2000), and the antiangiogenic effects of many compounds [such as ascorbic acid (Ashino et al, 2003), resveratrol (Lin et al, 2003) and NAC (Lin et al, 2003)] are achieved via their antioxidant properties. NAD(P)H oxidase, a major source of endothelial superoxide generation, is required for VEGF-induced endothelial cell proliferation and migration (Abid et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…20) On the other hand, the anti-angiogenic effects of typical antioxidants, such as ascorbic acid and vitamin E, are dependent on their antioxidative properties. 21,22) These reports indicate that ROS may be an important factor in angiogenesis. In the present study, we found that artepillin C and CAPE exhibited obvious antioxidative activity, and these compounds have also been reported to suppress angiogenesis in vitro and in vivo.…”
Section: Fig 3 Inhibitory Effects Of Brazilian and Chinese Propolismentioning
confidence: 96%